Landscape in the Spatial and Temporal Aspects of Settlement Systems in Kaliningrad Region - ROMANOVA, Elena A.; ZOTOV, Sergey I. (Journal of Environmental Management and Tourism, 2017)
The article describes the environmental factors that influence the formation of the settlement systems at the territory, and the degree of changes of this impact over time. Kaliningrad region is chosen as the study area, the settlement system is which evolved over many centuries. Over the past hundred years the settlement system, including the urban settlement, of the area reconstructed three times – as a result of the First World War, the German expansion to the east in 1939, and in the post-war period, while the overall pattern of settlements network maintained. A feature of the region is a complete change of population in the region since the end of World War II, accession of the former East Prussia to the Soviet Union, as part of the Russian Federation, which resulted in a fundamental change of economic system, determined features of the new building of settlements and areas of infrastructure development. Currently the regional settlement system shows, on the one hand, the similarities with the systems of settlement of other subjects of the Russian Federation, of the non-black soil zone of the Russian Plain, and on the other hand, is inherited from the system of settling the northern part of East Prussia. The degree of the landscape affects on the local systems of settlement is heterogeneous both spatially and temporally.